2007
DOI: 10.1186/bcr1732
|View full text |Cite
|
Sign up to set email alerts
|

Molecular response to aromatase inhibitor treatment in primary breast cancer

Abstract: Background Aromatase inhibitors such as anastrozole and letrozole are highly effective suppressants of estrogen synthesis in postmenopausal women and are the most effective endocrine treatments for hormone receptor positive breast cancer in such women. Little is known of the molecular effects of these agents on human breast carcinomas in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
96
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(112 citation statements)
references
References 47 publications
(55 reference statements)
15
96
0
1
Order By: Relevance
“…Basal specific genes in breast cancer cell lines included two isoforms of caveolin (CAV1 and CAV2), as well as VIM, LY6K and PRNP as previously described [28][29][30]. These genes correlate well with our previous reports of oestrogen responsive genes in primary breast cancers [19] and with genes associated with the basal-like phenotype of breast epithelial cells [26] and primary basal-like breast cancers [3]. The complete list of significant genes differentially expressed in luminal and basal-like cells are shown in Supplementary Tables S4A and S4B.…”
Section: Unsupervised Clustering Analysis Of Gene Expressionsupporting
confidence: 82%
See 3 more Smart Citations
“…Basal specific genes in breast cancer cell lines included two isoforms of caveolin (CAV1 and CAV2), as well as VIM, LY6K and PRNP as previously described [28][29][30]. These genes correlate well with our previous reports of oestrogen responsive genes in primary breast cancers [19] and with genes associated with the basal-like phenotype of breast epithelial cells [26] and primary basal-like breast cancers [3]. The complete list of significant genes differentially expressed in luminal and basal-like cells are shown in Supplementary Tables S4A and S4B.…”
Section: Unsupervised Clustering Analysis Of Gene Expressionsupporting
confidence: 82%
“…For expression microarrays, 1 lg of total RNA was T7 amplified by in vitro transcription using the amino allyl message Amp kit (Ambion), according to the manufacturer's instructions amplified RNA was then coupled to either Cy3 or Cy5 and hybridised against a reference RNA in separate dye-swap hybridisations [19]. Reference RNA comprised 33 RNA samples representing the majority of the cell lines used in the study and cell lines derived from purified non-tumour cell types as previously described [19].…”
Section: Microarray Platformsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sequential sampling of tumour during neoadjuvant treatment can be used to detect gene expression modification induced by therapy as we have demonstrated with endocrine therapy (Mackay et al, 2005). This was demonstrated for chemotherapy by Hannemann et al (2005), who observed that tumours that responded to neoadjuvant chemotherapy showed dramatic changes in their expression profiles when compared to the changes observed in non-responders (Hannemann et al, 2005).…”
Section: Discussionmentioning
confidence: 80%